2010
DOI: 10.4314/wsa.v36i5.61998
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical degradation of the antibiotic cephalexin in aqueous solution

Abstract: The degradation of cephalexin in aqueous solution under ultrasound irradiation was investigated. Biodegradability of the solution was evaluated by the BOD 5 /COD ratio, which was raised from zero to 0.36 after ultrasound treatment, indicating that the ultrasound irradiation process is a successful pre-treatment step to improve the biodegradability of cephalexin solution. The influences of ultrasound power and pH value on the degradation of cephalexin were studied. It was found that the optimal ultrasound power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The cephalexin was selected as a model to investigate the biodegradation of β-lactam antibiotics as function of β-lactamase, because Lin et al (2009) and Guo et al (2010) reported that the cephalexin is one of the most popular antibiotics that are ubiquitously present in sewage effluents at high concentrations due to its resistance to degradation during sewage treatment processes. The results found that 42 isolates presented high growth in the presence of 1 g L −1 of cephalexin.…”
Section: Discussionmentioning
confidence: 99%
“…The cephalexin was selected as a model to investigate the biodegradation of β-lactam antibiotics as function of β-lactamase, because Lin et al (2009) and Guo et al (2010) reported that the cephalexin is one of the most popular antibiotics that are ubiquitously present in sewage effluents at high concentrations due to its resistance to degradation during sewage treatment processes. The results found that 42 isolates presented high growth in the presence of 1 g L −1 of cephalexin.…”
Section: Discussionmentioning
confidence: 99%
“…If the e À /h + are not recombined, they have the chance to produce powerful oxidants cOH radicals, which in turn react with the pollutant molecules adsorbed on the surface of the photocatalyst and the oxidation reactions is initiated. 8 If the e À and h + recombine on the catalyst surface or in the bulk of the particles the energy will released as heat and degradation is not forwarded. To improve the degradation efficiency, recombination of e À /h + must be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used methods for removal of cephalexin are sunlight degradation, 3 Fenton oxidation, 4-6 adsorption 7 and advance oxidation processes. 8 In advance oxidation processes, a suitable photocatalyst is activated by incident light with energy higher or equal to the band gap energy of the photocatalyst, and then electron-hole pairs (e À /h + ) are generated. If the e À /h + are not recombined, they have the chance to produce powerful oxidants cOH radicals, which in turn react with the pollutant molecules adsorbed on the surface of the photocatalyst and the oxidation reactions is initiated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations